Transcatheter arterial chemoembolization for hepatocellular carcinoma: Comparison of the therapeutic efficacies between miriplatin and epirubicin. Issue 11 (18th September 2013) - Handa, Takahiro; Imai, Yukinori; Sugawara, Kayoko; Chikayama, Taku; Nakazawa, Manabu; Ando, Satsuki; Hamaoka, Kazuhiro; Inao, Mie; Nakayama, Nobuaki; Mochida, Satoshi
<x xml:space="preserve">Abstract</x> Aim The therapeutic efficacy of transcatheter arterial chemoembolization (TACE) using miriplatin was evaluated in comparison with that using epirubicin in patients with hepatocellular carcinoma (HCC). Methods Two hundred and eight‐nine HCC patients receiving TACE were retrospectively enrolled; none of the patients gave a previous TACE history. The short‐term therapeutic efficacy was evaluated by computed tomography (CT) performed 1 month later. In patients showing TE‐4, CT and/or magnetic resonance imaging examinations were performed repeatedly and the long‐term therapeutic efficacy was assessed based on local tumor recurrence. Results After exclusion of 68 patients (CT not performed at 1 month), 97 patients treated with epirubicin and 124 treated with miriplatin were analyzed. The percentage of patients showing TE‐4 was 46.8% in the miriplatin–TACE group, being significantly higher than that in the epirubicin–TACE group (33.0%). The cumulative local recurrence rates at 18 months were 71.2% in the miriplatin–TACE group and 43.1% in the epirubicin–TACE group; multivariate analysis revealed higher local tumor recurrence rates in the miriplatin–TACE group than in the epirubicin–TACE group. Conclusion For HCC patients, although miriplatin–TACE was superior to epirubicin–TACE in the short term, it proved inferior to the latter in the long term. The merits of TACE using miriplatin should be further investigated, because adverse effects appear to be minimal after miriplatin administration.